Under the same moon. The symbology of the moon in Li Bai and Federico García Lorca - Almendros Peñaranda, Rubén Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The aim of this study is to analyze the symbology of the moon in the literary works of the Chinese poet Li Bai and the Spanish writer Federico García Lorca. From the reading of a selection of texts, we will determine how the respective author’s cultural tradition –and particularly the conventional symbology of the moon– determines their transgression of the traditional norms and innovations in metaphor theory.
Keywords: Lorca; Li Bai; Chinese literature; moon; symbol; metaphor